The Relationship of Inflation and Economic Growth to the Financial Performance of the Makassar City Government - Alfi Widiyanti; Diah Retno Dwi Hastuti; Muhammad Syafri; Sri Astuty; Citra Ayni Kamaruddin (Jurnal Ekonomi Balance, 2025)
Financial performance is a measure of achievement in financial aspects including regional revenue and spending, so financial performance can be reflected in the increase in local revenue and regional spending efficiency (Lathifa & Haryanto, 2023). Financial performance measurement is very important to assess the accountability of local governments in their financial management. This study aims to analyze the relationship between inflation and economic growth on the financial performance of the Makassar City Government during the 2015–2024 period. The method used is a quantitative approach with secondary time series data, and an analysis technique in the form of a spearman rank correlation test, The results of the study show that both inflation and economic growth have a positive but weak relationship to very weak to very weak to the financial performance of the Makassar City government as indicated by the correlation value of > 0.05. This indicates that macroeconomic fluctuations are quite strong. The revenue structure, which is still highly dependent on central transfers, is one of the factors that explains the weak relationship between macroeconomic indicators and regional fiscal performance. Based on these findings, it is recommended to develop the research by including other variables beyond macroeconomic indicators such as regional investment levels, unemployment rates, the number of poor people, or the human development index (HDI). This variable reflects aspects of socio-economic development that can affect the financial performance of local governments, both directly and indirectly.